Analisis Strategi Pengendalian Banjir dengan Upaya Konservasi Air Menggunakan AHP: (Studi Kasus: Kota Tangerang dan Kabupaten Tangerang) - Cantik, Bella Koes Paulina; Fadilah, Shofwatul; Putri, Wike Andaresta Eka; Agustia, Daffira Ceisya Yourie (Universitas Kristen Maranatha, 2024)
). Several areas in Tangerang City and Regency are prone to flooding due to the high rainfall intensity, decreased drainage channel capacity, and reduced infiltration capacity. Water conservation can be an effort made to tackle these issues. This study aims to identify priority alternative measurements of flood control through water conservation implemented in the research area. This study uses a Quantitative Method by collecting data through questionnaires from 50 respondents experts in the fields of Civil Engineering, Urban Planning, Architecture, and Tourism residing in Tangerang City and Regency. The data collected were processed using the Analytical Hierarchy Process (AHP) Method to determine the best alternatives for flood control efforts through water conservation. The alternatives for flood control measures include watershed construction, infiltration wells construction, bio pores, naturalization, waste management, and urban forest development. Based on the data analysis, there are three dominant factors triggering floods in research area, namely land misuse, low soil infiltration, and high rainfall. Furthermore, three alternatives with the highest values from AHP Method, namely urban forest development, naturalization, and the construction of infiltration wells with values of 0,249; 0,182, and 0,172 respectively.